Agency: occupational therapists' perspectives on their sense of competence and their skills following training (Canadian Medical Education Journal, 2024)
Context. To tackle the systemic injustices experienced by people in vulnerable situations, occupational therapists' agency, i.e. their power to act, is necessary. However, occupational therapists feel ill-equipped to exercise this power, and would like to develop their skills. The general aim of this research was therefore to document occupational therapists' perception of their skills before and after agency training.Methods. We used a mixed sequential explanatory design, comprising a quantitative component consisting of a pre- and post-training self-administered questionnaire and a descriptive qualitative component with group interviews.Results. A total of 103 occupational therapists completed the training between January 19 and October 19, 2019. Their sense of competence improved, especially for those with no prior training in agency. The skills perceived as having developed the most corresponded to the skills deemed a priority for development, namely effective communication, intentional collaboration, and observation and analysis. On the other hand, occupational therapists emphasized that they had not mastered the exercise of these skills in a real-life context.Conclusion. Although continuing education is one way of improving the skills needed to exercise agency, questions remain as to the optimal modalities for ensuring their full and lasting development.